Introduction to adaptive lenses - Ren, Hongwen, 1964- (Wiley series in pure and applied optics., 2012)
"This is the first book to address the fundamental operation principles, device characteristics, and potential applications of various types of adaptive lenses. Setting out from basic material properties to device structures and performance, this volume covers solid lens, membrane lens, electro-wetting lens, dielectric lens, mechanical-wetting lens, and liquid crystal lenses. Potential applications of these adaptive lenses are also investigated, including image processing and zooming, optical communications, and biomedical imaging. This is an important reference for optical engineers, research scientists, graduate students and undergraduate seniors"--